ATP Released by Injured Neurons Activates Schwann Cells - Negro, Samuele; Bergamin, Elisanna; Rodella, Umberto; Duregotti, Elisa; Scorzeto, Michele; Jalink, Kees; Montecucco, Cesare; Rigoni, Michela (Frontiers in Cellular Neuroscience, 2016)
Injured nerve terminals of neuromuscular junctions (NMJs) can regenerate. This remarkable and complex response is governed by molecular signals that are exchanged among the cellular components of this synapse: motor axon nerve terminal (MAT), perisynaptic Schwann cells (PSCs), and muscle fibre. The nature of signals that govern MAT regeneration is ill-known. In the present study the spider toxin α-Latrotoxin has been used as tool to investigate the mechanisms underlying peripheral neuroregeneration. Indeed this neurotoxin induces an acute, specific, localized and fully reversible damage of the presynaptic nerve terminal, and its action mimics the cascade of events that leads to nerve terminal degeneration in injured patients and in many neurodegenerative conditions. Here we provide evidence of an early release by degenerating neurons of ATP as alarm messenger, that contributes to the activation of a series of intracellular pathways within SCs that are crucial for nerve regeneration: Ca2+, cAMP, ERK1/2, and CREB. These results contribute to define the cross-talk taking place among degenerating nerve terminals and PSCs, involved in the functional recovery of the NMJ.